FRI0177 Assessing the value of whole body magnetic resonance imaging as to clinical examination to predict remission and relapse in early peripheral spondyloarthritis. (12th June 2018) - Renson, T.; Carron, P.; Krabbe, S.; Jans, L.; De Craemer, A.-S.; de Hooge, M.; Jacques, P.; Ostergaard, M.; Elewaut, D.; Van den Bosch, F.
Abstract : Background: Evaluation of disease activity and treatment response in peripheral spondyloarthritis (pSpA) is currently based upon clinical findings, laboratory tests and ultrasound examination. Whole-body magnetic resonance imaging (WB MRI) is a relatively new imaging technique that could offer additional information regarding the inflammatory status of joints, entheses and soft tissues. Objectives: To determine A) the value of WB MRI, performed at baseline, in relation to clinical remission in pSpA and B) the value of subclinical inflammation, detected by WB MRI, at time of clinical remission in predicting flare after treatment withdrawal in pSpA. Methods: Clinical REmission in peripheral SPondyloArthritis (CRESPA) is a placebo-controlled trial of golimumab treatment in 60 early (symptom duration <12 weeks) pSpA patients (pts). All pts underwent a modified WB MRI at baseline and at the time of clinical remission when treatment was withdrawn. The WB MRI was performed by scanning multiple locations individually (using different coils) in order to investigate SpA-specific locations in detail. Several anatomical sites of pelvis and lower limbs were evaluated for bone marrow oedema (BME), synovitis and soft tissue inflammation (STI) by 3 readers, giving a score of 0 (no abnormalities), 1 (mild), 2 (moderate) or 3 (severe). For each site a mean of the scores of the 3 readers was calculated. For each patient at each time point, we calculated a sum score for synovitis, STI and BME separately adjacent to a total sum score. Changes scores are baseline minus remission sum scores. Results: Pts reaching clinical remission had significant lower baseline BME sum scores then the non-remission group (mean 1.86 vs. 2.89, p=0.024). At the time of clinical remission 10/45 (22%) and 11/45 (24%) pts had residual talocrural and subtalar synovitis respectively. However, there was no statistically significant difference between patients who relapsed after treatment withdrawal and those who remained in remission concerning synovitis sum scores (p=0.497) as well as BME sum scores (p=0.741) and STI sum scores (p=0.131) at time of clinical remission (table 1). Conclusions: Early pSpA pts who reach clinical remission have less BME on baseline WB MRI compared to those with ongoing disease activity. At time of clinical remission, a substantial part of the participants showed residual ankle synovitis on MRI. However, residual inflammatory lesions detected by WB MRI did not differ significantly between pts who relapsed after treatment withdrawal and those in ongoing clinical remission. Disclosure of Interest: None declared